Cognitive function and 99mTc-ECD brain SPECT are significantly correlated in patients with primary Sjögren syndrome: a case–control study. Issue 01 (21st January 2009) - Le Guern, V; Belin, C; Henegar, C; Moroni, C; Maillet, D; Lacau, C; Dumas, J L; Vigneron, N; Guillevin, L
Abstract : Objectives: To assess subclinical central nervous system (CNS) involvement in primary Sjögren syndrome (pSS), by comparing standard brain MRI, in-depth neuropsychological testing and 99m Tc-ECD brain single-photon emission computed tomography (SPECT) of patients with pSS with matched controls. Methods: 10 women (<55 years old), with pSS defined using European–American criteria, presence of anti-SSA and/or anti-SSB antibodies and no history of neurological involvement were prospectively investigated, and compared with 10 age- and sex-matched controls. All subjects underwent, within 1 month, brain MRI, neuropsychological testing, including overall evaluation and focal cognitive function assessment, and 99m Tc-ECD brain SPECT. Results: 99m Tc-ECD brain SPECT abnormalities were significantly more common in patients with pSS (10/10) than controls (2/10; p<0.05). Cognitive dysfunctions, mainly expressed as executive and visuospatial disorders, were also significantly more common in patients with pSS (8/10) than controls (0/10; p<0.01). Notably, between-group comparisons enabled a significant correlation to be established between neuropsychological assessment and 99m Tc-ECD brain SPECT abnormalities in patients with pSS (rs = 0.49, p<0.01). MRI abnormalities in patients and controls did not differ significantly. Conclusions: Neuropsychological testing and 99m Tc-ECD brain SPECT seem to be the most sensitive tools to detect subclinical CNS dysfunction in pSS. The strong correlation between cortical hypoperfusion in 99m Tc-ECD brain SPECT and cognitive dysfunction suggests an organic aetiology of CNS dysfunction in pSS. These data should be confirmed in a larger study.